Digitalisasi Wisata Halal melalui Penerapan QR Code Berbasis Website pada Agrowisata Kelurahan Lambung Bukit - Melladia, Melladia; Indah Febri Annisa; Dertha Mukhtar; Leila Muhelni (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
The Community-Based Empowerment Scheme Service Program within the scope of Community Partnership Empowerment aims to digitize the management of halal tourism at Agrowisata Lambung Bukit through the implementation of website-based QR Code technology. This service program was initiated by lecturers from Nahdlatul Ulama University of West Sumatra with the aim of increasing the efficiency of tourism data management and expanding the promotion of Agrowisata. The QR Code allows quick and efficient access to relevant information, such as details about the agrotourism managed by the Community Empowerment Forum partners in Lambung Bukit Subdistrict, Padang City. This system facilitates tourists in planning their visits while also assisting agrotourism managers in monitoring visitor data and optimizing services. Additionally, the website integrated with the QR Code functions as a digital marketing platform, reaching a wider audience, both local and international. The results of the program show that the use of website-based QR Codes successfully improved data management efficiency and strengthened the agrotourism’s position in attracting halal tourists. The application of this technology is expected to enhance the competitiveness of Lambung Bukit Subdistrict’s agrotourism and support local economic growth through increased tourist visits. This activity also involves training and mentoring to improve the partners’ knowledge and skills in digital management. The program results indicate increased management efficiency, expanded promotion, and support for local economic growth.